Synonymous codon usage in Thermosynechococcus elongatus (cyanobacteria) identifies the factors shaping codon usage variation - Prabha, Ratna (Biomedical Informatics, 2012)
Analysis of synonymous codon usage pattern in the genome of a thermophilic cyanobacterium, Thermosynechococcus elongatus BP-1 using multivariate statistical analysis revealed a single major explanatory axis accounting for codon usage variation in the organism. This axis is correlated with the GC content at third base of synonymous codons (GC3s) in correspondence analysis taking T. elongatus genes. A negative correlation was observed between effective number of codons i.e. Nc and GC3s. Results suggested a mutational bias as the major factor in shaping codon usage in this cyanobacterium. In comparison to the lowly expressed genes, highly expressed genes of this organism possess significantly higher proportion of pyrimidine-ending codons suggesting that besides, mutational bias, translational selection also influenced codon usage variation in T. elongatus. Correspondence analysis of relative synonymous codon usage (RSCU) with A, T, G, C at third positions (A3s, T3s, G3s, C3s, respectively) also supported this fact and expression levels of genes and gene length also influenced codon usage. A role of translational accuracy was identified in dictating the codon usage variation of this genome. Results indicated that although mutational bias is the major factor in shaping codon usage in T. elongatus, factors like translational selection, translational accuracy and gene expression level also influenced codon usage variation.